2016
DOI: 10.3390/chromatography3010001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Morphine and Its Metabolites in Human Urine by Capillary Electrophoresis with Laser Induced Fluorescence Detection Employing On-Column Labeling with a New Boronic Acid Functionalized Squarylium Cyanine Dye

Abstract: A novel method for the labeling and rapid separation of morphine, morphine-3-beta-Dglucuronide (M3G) and morphine-6-beta-D-glucuronide (M6G) in human urine employing a new boronic acid functionalized squarylium dye (SQ-BA3) and capillary electrophoresis with laser induced fluorescence detection (CE-LIF) is described. The spectrochemical properties, solution stability, pH range, and mechanisms for interactions with morphine and its metabolites were first established for SQ-BA3, followed by optimization of an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…According to the results obtained for both dyes, we can conclude that SQ‐BA4 showed to be a more stable dye either with or without HSA protein than SQ‐DBA2. These results are consistent with LOD results in the last section and also with the stability constant studies, which showed values of 3.67 × 10 6 M −1 and 1.17 × 10 5 M −1 for SQ‐BA4 and SQ‐DBA2, respectively. However, these stability constant results are shown to be superior to other reported stability constants for some squarylium dye–protein complexes, having higher concentrations of both the dye and HSA …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…According to the results obtained for both dyes, we can conclude that SQ‐BA4 showed to be a more stable dye either with or without HSA protein than SQ‐DBA2. These results are consistent with LOD results in the last section and also with the stability constant studies, which showed values of 3.67 × 10 6 M −1 and 1.17 × 10 5 M −1 for SQ‐BA4 and SQ‐DBA2, respectively. However, these stability constant results are shown to be superior to other reported stability constants for some squarylium dye–protein complexes, having higher concentrations of both the dye and HSA …”
Section: Resultssupporting
confidence: 92%
“…The limits of detection (LODs), calculated based on the signal to noise ratio, for HSA labeled in the case of on‐column mode with both SQ‐BA4 and SQ‐DBA2 dyes were relatively lower (more sensitive) than those for precolumn labeling. Also, the relatively low LOD for the protein complex with SQ‐BA4 is likely an indication of stronger protein–dye interactions than with SQ‐DBA2, which is in agreement with the higher value of the stability constant as determined previously for SQ‐BA4 with HSA . Also, limits of quantification (LOQs) in the case of on‐column mode with both dyes were one order of magnitude lower than those for precolumn labeling.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations